Antihypertensive Drug Deintensification and Recurrent Falls in Long‐Term Care. (23rd October 2018) - Song, Wei; Intrator, Orna; Lee, Sei; Boockvar, Kenneth
Abstract : Objective: To examine the relationship between antihypertensive drug deintensification and recurrent falls in long‐term care. Data Sources/Settings: Department of Veterans Affairs (VA) inpatient, outpatient, and purchased care data, Minimum Data Set assessments from VA nursing homes (NHs), and Medicare claims from fiscal years 2010 – 2015. Study Design: We identified NH residents with evidence of overaggressive antihypertensive treatment, defined as systolic blood pressure (SBP) 80–120 and an index fall. Recurrent fall, hospitalization, and mortality within 30 days were compared between veterans whose antihypertensive medications were deintensified versus those whose antihypertensive medications were not using propensity score methods (PSM). Principal Findings: Among 2, 212 NH residents with possibly overaggressive antihypertensive treatment, 11 percent experienced antihypertensive drug deintensification. Lower blood pressure, >1 antihypertensive drug, no congestive heart failure, fracture from index fall, and older age were associated with higher likelihood of deintensification. Antihypertensive deintensification was associated with statistically significant ( p ‐value < .01) lower risk of recurrent fall among residents with SBP 80–100 (marginal effect = −11.4 percent; PSM = −13.6 percent) and higher risk of death among residents with SBP 101–120 (marginal effect = 2.1 percent, p ‐value = .07; with PSM = 4.3 percent, p ‐value = .04). Conclusions: Results provide some needed evidence and guidelines for deintensifying antihypertensive medication among frail older residents; since hypertension is prevalent among 54 percent of NH residents, the potential impact of new evidence is great.